(untitled) (International Journal of Emerging Trends in Science and Technology, 2017)
This paper presents an insight into a proposal that intends to empowerment of women. It reflects on direct and indirect impacts of the initiative that targeted hundreds of women in Paramathi Velur, Namakkal District. The major aim of this paper is to promote social and economic empowerment of women. The key factors are that the ability of women to attaining knowledge and creation, personal and community development and as a whole women‟s development in the society. The research also examines the recent improvements in radio broadcast coverage and the information providing the women with a platform that adequately meets their needs.